Pengembangan Media Pembelajaran Happy Notes PERUGI (Perubahan Energi) Berbasis Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Ilmu Pengetahun Alam dan Sosial di Kelas IV Sekolah Dasar - Ratih Syalaisyah Az Zahra; Desi Wulandari (Postgraduate, University of Mataram, 2025)
Research at SD Negeri Wonosari 03 Semarang City identified the problem of limited concrete learning media and low student learning outcomes in Natural and Social Sciences subjects. To overcome this problem, the researcher developed and tested the Happy Notes PERUGI (Perubahan Energi) learning media based on Problem Based Learning. The method used is research and development (R&D) with the Borg and Gall model through 10 stages (research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational fiel testing, final product revision, dissemination and implemention) as well as data collection through observation, interviews, questionnaires, and documentation. The results of media validation by material and media experts show percentages of 83.3 and 87.5%, which are classified as very feasible. The calculation of N-Gain yields a value of 85.49%, with a high criterion. Thus, this learning media is declared to be very feasible and effective to improve the learning outcomes of grade IV students at SD Negeri Wonosari 03.